2021
DOI: 10.1097/jcma.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of intravitreal injections in response to the COVID-19 pandemic

Abstract: The Coronavirus disease 2019 (COVID-19) pandemic has caused unprecedented disruption to the normal operation of the healthcare system. On a worldwide scale, hospitals suspended nonurgent surgeries and outpatient visits to downsize clinical loadings to redistribute manpower to counteract the pandemic’s impact. So far, there is no evidence-based guideline defining a clear line between urgent and nonurgent indications of intravitreal injections (IVI). Herein, we aimed to summarize IVI algorithm modifications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
2
Order By: Relevance
“…The COVID-19 pandemic was a serious public health crisis at the time this study initiated. The pandemic has greatly decreased the administration of nonurgent procedures, resulting in the suspension or delay of intravitreal therapies [8, 9, 21]. Ryder et al [17] reported a mean interval of 15.6 days (range: 2–71 days) between DEX implantation in the initial eye and subsequent DEX implantation in the fellow eye.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic was a serious public health crisis at the time this study initiated. The pandemic has greatly decreased the administration of nonurgent procedures, resulting in the suspension or delay of intravitreal therapies [8, 9, 21]. Ryder et al [17] reported a mean interval of 15.6 days (range: 2–71 days) between DEX implantation in the initial eye and subsequent DEX implantation in the fellow eye.…”
Section: Discussionmentioning
confidence: 99%
“…Communication and co‐created treatment goal‐setting is obviously key, but can be complicated by hearing and/or cognitive impairment in this elderly population. Additionally, while several recent studies have investigated the effect of the COVID‐19 pandemic on treatment regimens and vision in nAMD (Arruabarrena et al, 2021 ; Bulut et al, 2021 ; Weng et al, 2021 ), we should also remember the impact of the recent pandemic on the mental health of our patients and our ability to provide the required level of physician–patient interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although we demonstrated no significant difference in vision loss because of those restrictions in a large cohort of patients, other studies have shown significant changes in BCVA or optical coherence tomography outcomes. [16][17][18][19][20] Possible explanations for this may be the size of the cohorts or the treatment regimen, which is mostly treat and extend, whereas other countries may apply monthly regimen, which may increase the difference in visual acuity because of an unplanned long break. Considering the above, it seems like the biggest unplanned added gap between anti-VEGF injections was two months long for most subjects, with a stable recovery since then.…”
Section: Discussionmentioning
confidence: 99%